Peculiarities of Investment Decision-making in the Oil and Gas Industry Aimed to Ensure Sustainable Growth of the Russian Economy - Perepelitsa, Denis Grigorievich; Zhdanova, Olga Aleksandrovna (International Journal of Energy Economics and Policy, 2017)
A dynamic analysis of the composition and structure of the oil and gas sector of the Russian economy was carried out in the study, a relationship between cyclical fluctuations of the world economy and energy prices was analyzed, and trends in world market prices for energy were studied. The authors identified basic systematic risks and uncertainties affecting investment decision-making in the Russian oil and gas sector and studied the peculiarities of making investment decisions. The academic novelty of the study is to propose specific ways to improve the investment decision-making of the Russian oil and gas business entities in the context of high macroeconomic risks to ensure sustainable growth of the Russian economy. The results obtained in the framework of the present study may be implemented by enterprises of the oil and gas industry and will also be of interest to other business structures in risk management, which is especially relevant in the context of high economic and geopolitical uncertainty. The paper presents mathematical models and justifies the choice of parameters to evaluate the fields taking the uncertainty into account. The approaches to formation of the investment decision-making policy based on real options method are proposed. Keywords: oil and gas sector, oil and gas investment projects, oil quotations, decision-making models, real options JEL Classifications: E3, Q4